Prevalence of depression and associated factors among people living with HIV/AIDS in public hospitals of Southeast Ethiopia - Fikreab Desta; Alelign Tasew; Yohannes Tekalegn; Demisu Zenbaba; Biniyam Sahiledengle; Tesfaye Assefa; Wogene Negash; Anwar Tahir; Tadele Regasa; Ayele Mamo; Zinash Teferu; Damtew Solomon; et al. (BMC Psychiatry, 2022)
Abstract Background Depression is the most frequent mental health condition among human immune deficiency virus or acquired immune deficiency syndrome (HIV/AIDS) patients. It has been related to negative health outcomes. This could lead to hospitalization and an increase in medical expenses. This study aimed to assess the prevalence of depression and associated factors among HIV/AIDS patients in public hospitals Bale Zone, Southeast Ethiopia. Methods A hospital-based cross-sectional study design was randomly employed among 554 study participants. A systematic random sampling technique was used to select the study subjects. A structured Patients Health Questionnaires- 9 was used to measure the depression status of HIV/AIDS patients. Data were collected using a pretested interviewer administered structured questionnaire as well as review of patients medical charts or records. Descriptive statistics were computed. Multivariable logistic regression analyses were conducted identify factors associated with the prevalence of depression. Adjusted odds ratio (AOR), along with a 95% confidence interval (CI), was used to estimate the strength of the association. A p-value of < 0.05 was considered statistically significant. Results The prevalence of depression among the study participants was found to be 44.9% (95% CI: 40.79%, 49.1%). Perceived HIV related stigma is the single most dominant predictor of depression [(AOR = 8.2, 95% CI: (4.96, 13.68)], low income level [(AOR = 3.1, 95% CI: (1.59, 6.22)] Experiencing any form of a side effect of highly active anti-retroviral therapy (HAART) [(AOR = 1.5, 95% CI: (1.04, 2.56)], having normal BMI [(AOR = 0.49, 95% CI: (0.29, 0.8)] being HIV patients at WHO clinical stage II [(AOR = 0.44, 95% CI: (0.22, 0.9)], were significantly associated with prevalence of depression. Conclusion The study revealed that the prevalence of depression among people living with HIV in the study settings was high, almost two out of every five HIV patients were depressed. Low income level, side effect to HAART, and having HIV related stigma were more likely to suffer from depression.